(untitled) (Baghdad Science Journal, 2024)
The present study aimed to investigate the possible production of Thioflavin T and the effect of NaCl concentrations and growth phases on the growth rate, doubling time and proline of C. saipanensis N. Hanagata (Scenedesmaceae, Shaerophleales). The alga was cultured in BG 11 medium and six NaCl concentrations were used in the experiments during different growth phases. The results have unveiled the presence of Triflavin T in the alga. The study results showed a growth rate decrease at all NaCl concentrations except in control treatment, while the doubling time, was recorded highest value (14 days) at the NaCl concentration of 0.08 M. The highest value of Proline (0.509 mg. Lˉ¹) was recorded at the treatment of 0.08 M of NaCl and recorded 0.3 mg. L-1 in the second phase of alga growth, and increased up to 0.695 mg. L-1in the interaction between NaCl concentrations and growth phases (0.08 M of NaCl and the second phase). The highest value of Thioflavin T (25.386 mg. Lˉ¹) was recorded at 0.005 M of NaCl and 21.937 mg. L-1 at the second phase of growth. While its concentration reaches 27. 335mg.L- in combined experiments (0.005 M of NaCl and the second phase of growth). Therefore, the results of this study unveiled the presence of Thioflavin T pigment in C. saipanensis. The NaCl concentrations and growth phases have an impact on the pigment and proline concentrations. This finding highlights the possible use of the alga to produce the Thioflavin T pigment for different purposes.